(untitled) (Journal of Engineering, 2008)
The aim of the present work is to study the effect of different outlet nozzle diameters, by using one or two nozzles on the performance of divergent vortex tube and also to determine the effects of various parameters on the vortex tube cooling performance such as: refrigeration capacity, coefficient of performance, isentropic efficiency. The experimental investigation was carried out on a divergent vortex tube rig manufactured for the present study covering all tests. The effect of different outlet nozzle diameters ( dn= 4 mm, dn = 5 mm, and dn= 6.5 mm) on the performance of the vortex tube is described by using one nozzle or two nozzles by varying the pressure of the inlet air and cold air mass ratio (μc) within the ranges (Pi abs=2 - 7 bar) and (μc= 0 - 1). The outlet nozzle diameter, (dn= 5 mm), and the outlet cold diameter (dc= 10 mm), when using two nozzles, give high temperature separation and may considered to be the optimum for different pressures of the inlet air regarding all the size tube diameter. The experimental study predicts two empirical results between the outlet nozzle diameter (dn), number of nozzles (N), inside vortex tube diameter (D), and length of vortex tube (L)